Predicción de mareas en el Lago de Maracaibo - Molines, Jean Marc (Rev. Téc. Fac. Ing. Univ. Zulia, 2011)
The tidal phenomenon, which produces a very important movement of ocean water masses, occurs for every coast of the world and specially for the Venezuelan coasts. The harmonic method, which derives from the tidal spectral theory, has been used to analyze tide gauge records for the Lake Maracaibo area. Computer tidal components for the analyzed tide guage are presented in the paper. The aplication to tidal prediction is also presented, with a set of comparation exaples beetween the prediction and in-situ data.